Development of Edpuzzle-Based Interactive Learning Media on Classification of Living Things Class VII - Meli Maria; Ari Sunandar; Hanum Mukti Rahayu (Jurnal Penelitian Pendidikan IPA, 2025)
Learning media used in SMP Negeri 3 Sungai Kakap in science lessons the use of learning media is still limited, the media used are whiteboards, textbooks, and the surrounding environment. This study aims to develop interactive learning media based on Edpuzzle for the classification of living things that is suitable for use, to determine students' responses to the media, and to analyse whether the media is effective in improving learning outcomes or student motivation. This research is a Research and Development (R&D) study using the ADDIE development model which consists of 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques using observation, interviews, questionnaires. Data analysis in this study used a Likert scale. Testing the validity of learning media includes material experts, media experts, and linguists. The research subjects consisted of 35 seventh-grade students from SMP Negeri 3 Sungai Kakap, divided into two groups: 10 students for the small-scale trial and 25 students for the large-scale trial. The grouping was done randomly while considering the students' academic abilities to ensure more representative research results. The results showed the acquisition of material expert validation of 88.63% (very valid), the results of media expert validation of 98.21% (very valid), the results of linguist validation of 93.33% (very valid), on a small-scale trial 10 students gave a response of 99.37% (very strong) and on a large-scale test 25 students gave a response of 96.56% (very strong). Based on these findings, it can be concluded that Edpuzzle-based learning media is declared valid, feasible for use, and effective in improving students' learning outcomes on the classification of living things material at SMP Negeri 3 Sungai Kakap.